«Taorifi muslimin» jurnalida turkistondagi islohotchilik jarayonlarining yoritilishi - Xasanov, A.O (SCIENCE and SOCIETY, 2024)
This article gives us a brief information about the journal "Taorifi Muslimin" which was published in Turkey at the beginning of the 20th century. Published articles in the journal are based on the history of Turkestan are analyzed and their statistics and content are here in revealed. This has shown that the journal is an important source for studying the political, social and cultural history of Turkestan.
Keywords: «taorifi muslimin» journal; national press; Istanbul; History of Turkistan; Isfandiyarkhan; Bukhara